The Supervision of Built Environment and Green Space Data Collection for Village’s Profile in Semangat Bakti Village, Barito Kuala - Caesarina, Hanny Maria; Rahmani, Dienny R (Comment: an International Journal of Community Development, 2019)
Abstract Land use in forms of built environment and green space is an essential element in urban and regional planning. This community service activity designed as a supervision for the people of Semangat Dalam Village to define built environment and green space area in the whole village. Participants were community and local people of Semangat Dalam Village. The tools and materials used in the supervision are a camera, a mini portable projector, laptop, and software: MS Office. The outcomes of this activity are the community can identify the positive and negative aspects of their village through data collection, therefore it can be used as a baseline to draw strategies for the future. A set of village profile was produced at the end of the supervision.